If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(15x+12)=(19x-24
We move all terms to the left:
(15x+12)-((19x-24)=0
We get rid of parentheses
15x-((19x-24)+12=0
| 49=-7(s-4) | | 10(x-4)=4(x+4)+4(x-2) | | 3x+5-x=3-(-6) | | 9h+45=8h | | 7x+32=5x | | 2+2x=14-x | | 50x+0=60x+60 | | 6(x-5)+4x=100 | | -24=9+3(c-6) | | 5=1/2d-3 | | 5d^2+15d+5=-6 | | y=6(45)+3 | | 7x+7=-9+5x | | a^2-15a+42=0 | | 1/7(4(x-1)=13)=x | | -63=-7(6+s) | | 1.6aa=1.2 | | 2m-3=5m | | 2+6n=-70 | | 45=6x+3 | | 4=-5b+b | | (3x+4x)=91 | | (J-6)=8h | | -2=3x-20÷4 | | -10(7n+2)=-10(9n+4) | | -8(t-4)-(t+8)=11 | | 7-5e=17 | | 1/3n-1/9=1/6n | | 60=15−5x | | (x-10)(3x+15)=300 | | 5-2(11+p)=1 | | 169=211-w |